PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERMAIN JAWABAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI DI KELAS X SMA NEGERI 10 PEKANBARU - Fitria Apriona; Elva Yasmi Amran; Lenny Anwar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The Research about application ofcooperative learning modelbermain jawabanhas beendonetoimprove student’s achievementon the topic ofnomenclature of compounds and chemical equations at 10th of SMA Negeri 10 Pekanbaru November 2013. This research is experimental research based on pretest-posttest design. The sample consisted of two classes, X.7classas control classandX.5classas experiment class that randomly selected after testing homogeneity. Cooperative learning model bermain jawaban applied in X.5. Analysis of data used t-test. Results of data processing obtainedtcount>ttable (4,04> 1,66). It means that the application of cooperative learning model bermain jawaban can improve student’s achievement on the topic of nomenclature of compounds and chemical equations at10th of SMA Negeri 10 Pekanbaru. The improvement of student’s achievement in experiment class was supported by N-Gain score 0,79 that included in high category.Keyword :Cooperative Learning, Bermain Jawaban, Nomenclature of Compounds and Chemical Equations